Is Preference for Monetary/Nonmonetary Rewards Related with the Level of Income? - Mitllari, Eralda; Kasimati, Mimoza (European Scientific Journal, ESJ, 2019)
Employees’ motivation is a very important issue that every organization should consider, as it increases the chances to attract and retain valuable individuals and achieve performance. Although aware of the advantages, managers sometimes do not put great effort into it. Sometimes, it is just difficult to address it properly because of the diversity within the organizations. Researchers have been discussing a lot about how to motivate, about monetary and nonmonetary rewards, etc., and how the method should consider factors related to the individual to be motivated among other things. This paper show the results of a study conducted with employees of the private banking sector in Albania, and shows that employees of this sector are more motivated by monetary than non-monetary rewards. There is no enough evidence to support the relation of monthly level of income and motivation from either monetary or non-monetary rewards.